Controlador MRAC-SM aplicado a um conversor QUASI-Z-SOURCE fotovoltaico conectado à rede monofásica - Hollweg, Guilherme Vieira (2019)
This dissertation deals with the design and development of an Adaptive Control by Model Reference (MRAC) structure together with a Sliding Mode (SM) controller through a simplified first order reference model, neglecting non-dominant dynamics in the system’s plants. This control strategy is developed for a photovoltaic grid-connected quasi-Z-Source inverter with LCL filter. Throughout the text, its discussed the modeling of the DC-AC converter, the design of the elements that make up the system, as well as the analysis of the plants. The design and development of a MRAC-SM structure for the DC side and the AC side of the analyzed inverter will be presented. Offline simulation results and practical results in Hardware in the Loop are presented to show the difference and advantages of this control strategy compared to a conventional controller, widely studied in the literature.